HUBUNGAN GANGGUAN MENTAL EMOSIONAL DENGAN KECANDUAN MEDIA SOSIAL PADA MAHASISWA SEMESTER 1 TAHUN AJARAN 2019 DAN SEMESTER 3 TAHUN AJARAN 2018 DI UNIVERSITAS DIPONEGORO SEMARANG - Mahardhika, Alain Stephano; Fitrikasari, Alifiati; Wardani, Natalia Dewi; Hadiati, Titis; Sutaty, Witrie; Julianti, Hari Peni (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background: Currently the level of addiction to social media tends to increase, especially among students. 75% of individuals who experience internet addiction are caused by problems in their relationships with other people. One of the related factors is emotional mental disorder. Objective: To determine the relationship between mental emotional disorders and social media addiction in students in the 1st semester of the 2019 academic year and the 3rd semester of the 2018 academic year at Diponegoro University, Semarang. Methods: Research with cross sectional design. The research sample is Diponegoro University Semarang students in 1st semester of the 2019 academic year and 3rd of the 2018 academic year. The independent variable is mental emotional disorder, while the dependent variable is social media addiction. The research instrument used a sociodemographic questionnaire, the Bergen Social Media Addiction Scale (BSMAS) and the Self Reporting Questionnaire 20 (SRQ20). Research variables were analyzed by chi square test. Results: The majority of research subjects had normal emotional mental disorders as many as 140 (82.8%) and 29 (17.2%) indicated experiencing emotional disorders. The majority of social media addiction levels were normal as many as 113 (66.9%), while alerts were 56 (33.1%), There was a relationship between emotional mental disorders and social media addiction (p=0.019, PR=2.587 95%CI=1.146 – 5,840). Conclusion: There is a significant relationship between mental emotional disorders and social media addiction. Diponegoro University Semarang students in 1st semester of the 2019 academic year and 3rd semester of the 2018 academic year.